(untitled) (Indian Journal of Animal Production and Management, 2014)
The present investigation was conducted to study some economic traits of dairy cattle and buffalo under tribal and non-tribal area of Udaipur district. In Udaipur district four tehsils were selected for sampling under rural areas which included tribal and non- tribal villages. Sixteen villages (eight tribal and eight non-tribal’s) were randomly selected from each tehsils. Thirty dairy farmers’ families were selected in each village. An interview schedule was developed for relevant information on the different aspects of dairy cattle and buffaloes management in tribal and non-tribal households. Majority of farmers (74.70 %) in tribal were do not followed deworming practices. The association castration system of male calf between tribal and non- tribal animals was found to be significant. Only 4.16 % farmers followed AI services to serve their cattle and buffalo in tribal areas in contrast to 31.66 percent in non-tribal areas. The average age at first calving was found to be 5.89 ± 0.71 and 5.30 ± 0.79 years in non-descript cows, 4.79± 1.07 and 4.92± .043 in crossbreed cows in tribal and non-tribal households respectively. The average mean calving intervals was 23.46 ± 4.56 and 20.94 ± 5.70 month in nondescript cows in tribal and non tribal area respectively. Significantly (P<0.05) difference was observed in total milk yield between tribal (492.32 ± 72.70 kg ) and non-tribal (523 ± 99.15 kg ) cows .